Patient-reported outcomes of serum eye drops manufactured from Australian blood donations and packaged using Meise vials - Gemelli, Carley N.; Mondy, Phillip; Kakkos, Athina; O’Donovan, Justine; Diaz, Perfecto; Knight, Elizabeth; Hirani, Rena (Frontiers in Medicine, 2023)
Introduction Serum eye drops (SED) are an effective treatment for dry eye syndrome. However, autologous serum collection can have challenges. Patient-tailored (allogeneic) SED (PT-SED) can be made from healthy blood donors. Australian Red Cross Lifeblood has manufactured both autologous SED (Auto-SED) and PT-SED and, in May 2021, introduced Meise vial packaging. This study aimed to explore SED patient-reported outcomes and vial packaging satisfaction. Methods A prospective cohort study was conducted with recruitment between 1 November 2021 and 30 June 2022. Participants completed the dry eye questionnaire (DEQ5), health-related quality-of-life (SF-8™), functional assessment of chronic illness therapy-treatment satisfaction-general (FACIT-TS-G), and general wellbeing surveys. Existing patients completed these once, and new patients were surveyed at baseline, 3 months post-treatment, and 6 months post-treatment. Results Participants who completed all study requirements were 24 existing and 40 new Auto-SED and 10 existing and 8 new PT-SED patients. Auto-SED patients were younger [56.2 (±14.7) years] than PT-SED patients [71.4 (±10.0) years]. Participants used a mean of 1.8 (±1.1) SED, 5.3 (±2.9) times per day. In new patients, DEQ5 scores improved within 6 months from 14.0 (±2.9) to 10.6 (±3.4) for Auto-SED and from 12.9 (±3.7) to 11.4 (±2.8) for PT-SED. General wellbeing measures improved in the new Auto-SED from 7.0 (±1.9) to 7.8 (±1.7) but were reduced for new PT-SED from 6.7 (±2.9) to 6.1 (±2.9). Discussion SED improved dry eye symptoms in most patients, regardless of the serum source. Patients using PT-SED showed decreases in some quality-of-life measures; however, recruitment was reduced due to operational constraints, and concurrent comorbidities were not assessed. General feedback for SED and vial packaging was positive, with some improvements identified.